EPR-ENDOR characterization of (17O, 1H, 2H) water in manganese catalase and its relevance to the oxygen-evolving complex of photosystem II. - McConnell, I; Grigoryants, V; Scholes, C; Myers, W; Chen, P; Whittaker, J; Brudvig, G (2012)
The synthesis of efficient water-oxidation catalysts demands insight into the only known, naturally occurring water-oxidation catalyst, the oxygen-evolving complex (OEC) of photosystem II (PSII). Understanding the water oxidation mechanism requires knowledge of where and when substrate water binds to the OEC. Mn catalase in its Mn(III)-Mn(IV) state is a protein model of the OEC's S(2) state. From (17)O-labeled water exchanged into the di-μ-oxo di-Mn(III,IV) coordination sphere of Mn catalase, CW Q-band ENDOR spectroscopy revealed two distinctly different (17)O signals incorporated in distinctly different time regimes. First, a signal appearing after 2 h of (17)O exchange was detected with a 13.0 MHz hyperfine coupling. From similarity in the time scale of isotope incorporation and in the (17)O μ-oxo hyperfine coupling of the di-μ-oxo di-Mn(III,IV) bipyridine model (Usov, O. M.; Grigoryants, V. M.; Tagore, R.; Brudvig, G. W.; Scholes, C. P. J. Am. Chem. Soc. 2007, 129, 11886-11887), this signal was assigned to μ-oxo oxygen. EPR line broadening was obvious from this (17)O μ-oxo species. Earlier exchange proceeded on the minute or faster time scale into a non-μ-oxo position, from which (17)O ENDOR showed a smaller 3.8 MHz hyperfine coupling and possible quadrupole splittings, indicating a terminal water of Mn(III). Exchangeable proton/deuteron hyperfine couplings, consistent with terminal water ligation to Mn(III), also appeared. Q-band CW ENDOR from the S(2) state of the OEC was obtained following multihour (17)O exchange, which showed a (17)O hyperfine signal with a 11 MHz hyperfine coupling, tentatively assigned as μ-oxo-(17)O by resemblance to the μ-oxo signals from Mn catalase and the di-μ-oxo di-Mn(III,IV) bipyridine model.